CPWF Annual Report 2008 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2009)
Through its innovative operations, and its facilitation of dynamic communities of researchers, development experts, policy makers, producers and consumers, this CGIAR Challenge Program goes beyond research for development as usually practiced. Yet, paradoxically for a program well-versed in technical and social complexity, the CPWF approach is simple: to effectively address a shared problem, we must first work together. 2008 CGIAR Annual Report."